2003
DOI: 10.1177/153944920302300402
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Upper Extremity Strength and Instrumental Activities of Daily Living Performance among Elderly Women

Abstract: The purpose of this study was to assess therelationship between upper extremity strength and the ability to perform instrumental activities of daily living (IADL) independently and to explore how therapists might interpret the results of upper extremity strength evaluations among elderly women. Participants included 29 women (68 to 84 years old) who resided in assisted living facilities. Daily living performance was assessed using five subscales of the Multilevel Assessment Instrument. Grip, lateral pinch, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…Two of these trials show that such effect can be sustained for 6 months [11,8]. Although age-related decline in muscle strength is strongly related to functional decline in older adults [19,25,24,36,41,23], the process of aging also influences other motor elements that are essential for ADL performance such as coordination [44]. If the training only targets one essential body motor element and ignore other elements, the training effect on ADL may be compromised.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two of these trials show that such effect can be sustained for 6 months [11,8]. Although age-related decline in muscle strength is strongly related to functional decline in older adults [19,25,24,36,41,23], the process of aging also influences other motor elements that are essential for ADL performance such as coordination [44]. If the training only targets one essential body motor element and ignore other elements, the training effect on ADL may be compromised.…”
Section: Discussionmentioning
confidence: 99%
“…Age-related loss in muscle strength can jeopardize this ability and lead to disability [19,25,24,36,41,23]. For example, the progression of muscle weakness limits the ability to grasp an object which further impedes the ability to open a jar.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For women, especially those who reside alone, maintaining independence with meal preparation contributes to their ability to successfully age in place (Feldman, Hollander, & Oberlink, 2003). When a decline in functional capacity related to aging or disease occurs, a previously enabling home environment may no longer facilitate safe and independent participation in instrumental activities of daily living (IADL) (Gitlin, Mann, Machiko, & Marcus, 2001;McGee & Mathiowetz, 2003;Sixsmith & Sixsmith, 2008), which may lead to placement in some form of supervised living environment. The number of American women who want to age in place is large; over 83% of Americans who are 45 years of age or older desire to age in place (American Association of Retired Persons, 2000).…”
Section: Aging In Placementioning
confidence: 99%
“…The action of large muscle groups, especially in the upper extremities, is necessary for daily tasks such as carrying, pulling and pushing [1]. Previous research has shown that upper extremity muscle weakness can limit activities of daily living, particularly in the use of instruments [4]. The muscle strength of the upper limbs must be supported to enable skilled hand function, and the muscles of the upper limb are necessary to properly adjust the other joints of the arms, provide hand stability, and perform delicate tasks.…”
Section: Introductionmentioning
confidence: 99%